(untitled) (The Pakistan Development Review, 1995)
Earlier neoclassical, classical, or structuralist theories [due to Rostow (1960)] considered economic growth to be a result of the right quantity and combination of saving, investment, and foreign aid, with surpluses from the primary commodityproducing sectors being channelled into capital for further growth. Accordingly, the main constraint in these growth models has been the relatively low level of capital formation available. While the above paradigm has intuitive appeal, it, however, ignores the complementarity of social-political influences on the physical variables (i.e., capital, labour, etc.) in growth and development. Urquidi (1971) argued that the social progress of a nation is a necessary condition for sustained economic growth. It is now increasingly evident that the investment in the social sectors-primary education, basic health, housing, changes in land-tenure system, social security, better social relations-are as, if not more, important than the investment in the commodity-producing sectors or related infrastructure. In this context, Lloyd-Ellis (1993) noted: